Film thickness dependent microstructural changes of thick copper metallizations upon thermal fatigue. Issue 11 (13th June 2017) - Bigl, Stephan; Trost, Claus O.W.; Wurster, Stefan; Cordill, Megan J.; Kiener, Daniel
Abstract: Abstract : With increasing performance requirements in power electronics, the necessity has emerged to investigate the thermo-mechanical behavior of thick Cu metallizations (≥5 µm). Cu films on rigid substrates in the range of 5–20 µm were thermally cycled between 170 and 400 °C by a fast laser device. Compared to the initial microstructures, a texture transition toward the {100} out-of-plane orientation with increasing film thickness was observed during thermo-mechanical cycling, along with an abnormal grain growth in the {100}-oriented grains and a gradual development of substructures in a crystallographic arrangement. Compared to the well-studied thin Cu film counterparts (≤5 µm), the surface damage showed a 1/ h f dependency. Transition from an orientation independent ( h f = 5 µm) to an orientation specific thermo-mechanical fatigue damage ( h f = 10, 20 µm) was observed following a higher damager tolerance in {100} oriented grains.